(untitled) (Research, Society and Development, 2020)
The aim was to conduct a literature review on the estrus detection and its interference on the reproductive efficiency of dairy cattle. Efficient and accurate estrus detection of cattle and artificial insemination in an assertive time are essential to increase pregnancy rate, estrus detection rate, and consequently good reproductive efficiency. Methods of estrus detection that are widely used on farms do not have good rates. This is because the physiological and behavioral changes of the animals, as well as the period of the duration of the estrus cycle, are being expressed in low intensity and short duration. In addition, they are very variable and difficult to measure. Thus, it is of utmost importance to use electronic methods to improve estrus detection.